The Increase of Gross Motoric Ability of Group B Students through Laciba Exercise Activity in Tk Dharma Indria 1 Patrang Jember Academic Year 2016/2017 - Khutobah Khutobah; Nanik Yuliati; Misno Abdul Lathief; Norma Wahyu Pristina (Pancaran Pendidikan, 2018)
This research was carried out because the learning activities used by the teacher were less varied, which resulted in abusive motor skills of group B's children not yet well developed. The purpose of this study is to improve the abusive motor skills of children through laciba gymnastic activities. The type of research used is classroom action research (PTK) which is implemented in two cycles. The subjects of the study were children of group B in TK Dharma Indria 1 amounting to 26 children consisting of 11 boys and 15 girls. Methods of data collection used are observation, documentation, interviews, and performance tests. The results showed that motor abusive ability of group B children in TK Dharma Indria 1 had improved with very good qualification. The average value of the class at pre-cycle 46.15, in the first cycle 61.77, and in the second cycle increased to 86.77.